(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To compare the safety and efficacy of percutaneous nephrolithotomy (PCNL) and open surgery in the treatment of patients having large kidney stone(>2 cm ). Materials & Methods: A Randomised controlled clinical trial (RCT ) of 80 patients diagnosed with kidney stone disease admitted in the NIKDU during the period of Jan’ to Dec’2009 were divided conveniently into two groups. Intervention was done in the form PCNL(40) and open surgery (40). Clinical outcome like, peroperativecomplications,durationof surgery,mean hospital stay,convalescence period, amount of analgesia required to relief pain, stone clearance rate were reviewed and compared between the groups. There was no significant difference in preoperative variables such as age,sex, stone size in cm, stone number- single/multiple and stag horn Stone. Results: There were statistically significant difference in the parameters between the groups,( PCNL vs open surgery [mean ± SD]): duration of operation (min), 97.90 ± 24.89 vs 136.62 ± 23.54, postoperative hospital stay (days) ,4.77 ± 3.98 vs 9.55 ± 3.65, mean time return to work (days) , 3.09 ± 1.21vs 6.25 ± 1.53, ( p value is <0.001). Intraoperative complications like bleeding requiring blood transfusion are significantly lower in PCNL (11 cases 34.1%) than in open surgery( 18 cases 45.0%), (Chi-square = 4.82; p = 0.049). Conclusion: PCNL is relatively safe & better treatment option than open surgery in the treatment of large renal calculi, It has definite advantages of statistically less peroperative bleeding and lower morbidity. Bangladesh Journal of Urology, Vol. 17, No. 2, July 2014 p.71-74